Quantifying gravity wave momentum fluxes with mesosphere temperature mappers and correlative instrumentation - Fritts, David C.; Pautet, P. Dominique; Bossert, Katrina; Taylor, Michael J.; Williams, Bifford P.; Iimura, Hiroyuki; Yuan, Tao; Mitchell, Nicholas J.; Stober, Gunter (Journal of Geophysical Research: Atmospheres, 2014)
An Advanced Mesosphere Temperature Mapper and other instruments at the Arctic Lidar Observatory for Middle Atmosphere Research in Norway (69.3°N) and at Logan and Bear Lake Observatory in Utah (42°N) are used to demonstrate a new method for quantifying gravity wave (GW) pseudo-momentum fluxes accompanying spatially and temporally localized GW packets. The method improves on previous airglow techniques by employing direct characterization of the GW temperature perturbations averaged over the OH airglow layer and correlative wind and temperature measurements to define the intrinsic GW properties with high confidence. These methods are applied to two events, each of which involves superpositions of GWs having various scales and character. In each case, small-scale GWs were found to achieve transient, but very large, momentum fluxes with magnitudes varying from ~60 to 940 m 2 s 2 , which are ~1–2 decades larger than mean values. Quantification of the spatial and temporal variations of GW amplitudes and pseudo-momentum fluxes may also enable assessments of the total pseudo-momentum accompanying individual GW packets and of the potential for secondary GW generation that arises from GW localization. We expect that the use of this method will yield key insights into the statistical forcing of the mesosphere and lower thermosphere by GWs, the importance of infrequent large-amplitude events, and their effects on GW spectral evolution with altitude.